ChemInform Abstract: Myrtanyl‐Prolinamide: A New Chiral Organocatalyst for Stereoselective Aldol Reactions. Issue 37 (September 2015) - Kumar, Togapur Pavan; Shekhar, Rapelli Chandra; Sunder, Kondepudi Sugnana; Vadaparthi, Rajesh
Abstract Newly synthesized myrtanyl‐prolinamide is used for the stereoselective organocatalytic direct aldol reaction of various aryl aldehydes with ketones.